Construction of Nonenzymatic Flexible Electrochemical Sensor for Glucose Using Bimetallic Copper Ferrite/Sulfur-Doped Graphene Oxide Water-Based Conductive Ink by Noninvasive Method - Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (AMER CHEMICAL SOC, 2025)
Diabetes is a chronic disease that results in elevated blood glucose levels due to insufficient insulin production by the pancreas or impaired insulin utilization by the body. The development of effective tools for the in vitro detection of blood glucose is of paramount importance. Flexible electrodes serve as indispensable components in point-of-care systems, thus increasing accessibility and personalization in health monitoring. We present the preparation of handmade screen-printed electrode with water-based conductive ink for in vitro nonenzymatic glucose (Glu) determination at physiological pH values. The investigation aimed to identify the optimal conditions for formulating and composing the conductive ink used to create a copper ferrite/sulfur-doped graphene oxide/graphite/screen-printed electrode (CuFe2O4/S-GO/G/SPE). The resulting CuFe2O4/S-GO/G/SPE shows excellent glucose sensing ability with a limit of detection (LOD) of 2.93 mu M. The superior determination at physiological pH is attributed to the complex structure formed by CuFe2O4 nanoparticles with glucose molecules in the basic pH conductive ink structure. Additionally, the excellent delocalization and conductivity of the S-GO particles in this complex structure contribute to improved performance. The study on artificial sweat samples resulted in achieving recovery values of 96.60% to 104.97%. In conclusion, the nonenzymatic and noninvasive Glu sensor printed with conductive ink containing CuFe2O4/S-GO/G on a flexible paper substrate surface demonstrated remarkable capabilities for determining Glu levels in artificial sweat samples. SPEs prepared with conductive ink produced by using these materials are promising candidates for use as electrodes in flexible and wearable sensor technology.
Keywords: Glucose; nonenzymatic; flexible sensor; screen printed electrode; wearable sensor; SCREEN-PRINTED ELECTRODES; SOLVOTHERMAL SYNTHESIS; PERFORMANCE; CUO; COMPOSITES; PHASE; IONS; Science & Technology - Other Topics; Materials Science